The Danish labor market, 2000-2022 - Torben M. Andersen (IZA World of Labor, 2023)
Denmark is often highlighted as a "flexicurity" country with lax employment protection legislation, generous unemployment insurance, and active labor market policies. This model has coped with the Great Recession and the Covid-19 pandemic, avoiding large increases in long-term and structural unemployment. The recovery from Covid-19 alongside re-openings has been swift, so labor market effects were temporary. A string of recent reforms has boosted labor supply and employment; although fiscal sustainability is ensured, demographic changes challenge the labor market. Real wage growth has been positive and responded-with some lag-to unemployment.
Keywords: F44; L1; J1; J6; J61; 330; flexicurity; business cycles; structural policies; youth unemployment; immigration